AQLLI HAVO TORTGICH LOYIHASI - Artikbayev, M.A.; Azbergenova, N.K. (SCIENCE and SOCIETY, 2025)
Today, the topic of «Gas Diffusion» holds significant importance in social, economic, and environmental fields. This issue is primarily characterized by the spread of carbon monoxide. Carbon monoxide poisoning can lead to human intoxication and even death. Therefore, preventing the spread of carbon monoxide has become a global problem, and various measures are being taken to address it. One such measure is the development of the «Smart Exhaust Fan» project. The purpose of this project is to prevent the spread of carbon monoxide in case the flame on a gas stove goes out, automatically extract the air, shut off gas pipelines to ensure safety, and promptly notify the homeowner.